2011
DOI: 10.1016/j.pbi.2011.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Plant NB-LRR signaling: upstreams and downstreams

Abstract: Plant disease resistance proteins commonly belong to the nucleotide binding-leucine rich repeat (NB-LRR) protein family. These specialized immune proteins mediate recognition of diverse pathogen-derived effector proteins and initiate potent defense responses. NB-LRRs exhibit a multidomain architecture and each domain appears to have discrete functions depending on the stage of NB-LRR signaling. Novel proteins that were found to interact with the core HSP90 chaperone complex regulate accumulation and activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
86
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(88 citation statements)
references
References 53 publications
1
86
0
1
Order By: Relevance
“…Perception of feeding behavior by plants with R gene was shown to activate phytohormone, salicylic acid (SA)-dependent signaling cascade and callose deposition [14]. The detailed signaling cascades involving NB-LRR motif has been thoroughly summarized in the context of disease resistance [15,16] and plant-aphid interactions [2] suggesting that the induced defense responses involve multiple signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Perception of feeding behavior by plants with R gene was shown to activate phytohormone, salicylic acid (SA)-dependent signaling cascade and callose deposition [14]. The detailed signaling cascades involving NB-LRR motif has been thoroughly summarized in the context of disease resistance [15,16] and plant-aphid interactions [2] suggesting that the induced defense responses involve multiple signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%
“…The signaling events activated by well-studied bacterial flagellin and elongation factor Tu include rapid receptor dimerization, phosphorylation, and ubiquitination, which lead to oxidative burst, stomatal closure, induction of defense-related genes, and accumulation of antimicrobial compounds. In addition to PTI, plants have also evolved resistance proteins that directly or indirectly recognize cognate pathogen-encoded effectors and result in cultivar-specific effector-triggered immunity often accompanied by localized programmed cell death or hypersensitive response (HR) and systemic defense signaling (DeYoung and Innes, 2006;Bent and Mackey, 2007;Elmore et al, 2011;Maekawa et al, 2011;Bonardi et al, 2012). In order to successfully colonize plant tissue and cause disease, pathogens need to avoid and/or suppress host immune systems and obtain nutrients before they can multiply to high levels.…”
mentioning
confidence: 99%
“…Structural analyses of NB-LRR proteins have indicated that the C-terminal LRR domain confers recognition specificity, while the central NB domain plays a role in regulation and possibly downstream signaling (Rairdan et al, 2008;Elmore et al, 2011;Takken and Goverse, 2012). The variable N termini have been implicated in at least two key NB-LRR functions.…”
mentioning
confidence: 99%